The evolution of destination branding: A review of branding literature in tourism - Marta Almeyda-Ibáñez; Babu P. George (Journal of Tourism, Heritage & Services Marketing, 2017)
Tourism is a promise and destinations communicate the credibility of that promise by means of destination brands. Branding has become a key tool for tourism destinations to make explicit the complexity of experiences to be expected by tourists visiting a destination. This paper provides a comprehensive literature review of various issues associated with tourism destination branding. It brings together a wide range of debates in the generic marketing literature, places them alongside the nuances of tourism, and thereby identifies unique challenges of branding in tourism destination contexts. Finally, a case study of USP based national tourism branding campaigns in the Caribbean is presented.